2014
DOI: 10.1146/annurev-clinpsy-032813-153626
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Use in Pregnant and Postpartum Women

Abstract: Women in their reproductive years are at increased risk of experiencing depressive and anxiety disorders. As such, it is likely that pregnant women will undergo treatment with antidepressants. We review the risk of adverse pregnancy outcomes and perinatal and neonatal complications of the offspring related to in utero exposure to antidepressants. The literature shows that antidepressant exposure is associated with fetal growth changes and shorter gestations, although effects are small. There are a number of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(54 citation statements)
references
References 115 publications
(241 reference statements)
2
45
3
1
Order By: Relevance
“…27,28,32 Although there are conflicting reports published, a greater number of studies on the use of paroxetine describe deleterious effects such as increased risk of cardiac malformations. 24,[26][27][28]31,[33][34][35] This increased risk is also supported by two recent meta-analyses (reported OR = 1.43, 95%CI 1.08-1.88 and 1.44, 95%CI 1.12-1.86). 27,28 The OR for the same defects in fluoxetine users was reported to be 1.17-1.60 by three meta-analyses.…”
Section: Congenital Malformationsmentioning
confidence: 58%
See 3 more Smart Citations
“…27,28,32 Although there are conflicting reports published, a greater number of studies on the use of paroxetine describe deleterious effects such as increased risk of cardiac malformations. 24,[26][27][28]31,[33][34][35] This increased risk is also supported by two recent meta-analyses (reported OR = 1.43, 95%CI 1.08-1.88 and 1.44, 95%CI 1.12-1.86). 27,28 The OR for the same defects in fluoxetine users was reported to be 1.17-1.60 by three meta-analyses.…”
Section: Congenital Malformationsmentioning
confidence: 58%
“…48,49,64 Data are also conflicting regarding the relationship between antenatal antidepressant exposure and other neonatal outcomes such as spontaneous abortion, birth weight, persistent pulmonary hypertension, and autism spectrum disorders. 23,26,35,47,[50][51][52][53][54][55][56][57]60,[65][66][67][68][69] Specific information on the risk of other neonatal outcomes in fetuses exposed to clomipramine is lacking. The limited available data suggest that similar to SSRIs, TCAs may be associated with PTB and PNAS.…”
Section: Congenital Malformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in terms of major malformations, no specific pattern has been consistently associated with ADs, with the possible exception of paroxetine and cardiac malformations 18. It is generally reported that AD exposure may be associated with a significant increased risk of spontaneous abortion, preterm birth and infants born weighing less than 2500 g 17 19…”
Section: Harmful Effects Of Antidepressants During Pregnancy: Neonatamentioning
confidence: 99%